ChemInform Abstract: Asymmetric Aldol Reaction of Thiazole‐Carbaldehydes: Regio‐ and Stereoselective Synthesis of Tubuvalin Analogues. Issue 16 (April 2015) - Paladhi, Sushovan; Das, Joydeb; Samanta, Mousumi; Dash, Jyotirmayee
Abstract Tubuvalin derivatives are prepared by a regio‐ and enantioselective L‐proline‐catalyzed aldol reaction of thiazole carbaldehydes with acetone and a corresponding prolinamide‐catalyzed transformation of 2‐formylthiazole‐4‐carboxylate with methylisopropyl ketone on water.